ANALISIS PEMASARAN BIJI KAKAO DI KECAMATAN PAYAKUMBUH SELATAN KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Nurjannah.A, Yesi; Tety, Ermi; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) to analyze marketing functions and marketing channels; (2) to analyze the marketing costs, margins, profit, farmer's share and marketing efficiency and (3) to identify the problems faced by each institution marketing. The research method used is survey method with a number of samples are 40 cocoa farmers, 6 collecting traders and 3 wholesalers. The results showed that marketing functions are carried out by institutions involved in the marketing of cocoa beans, namely the farmers, traders and wholesalers covering exchange function, physical function and function facilities. Cocoa marketing channels in South Payakumbuh District consists of three channels in which channel I farmers sell their cocoa beans to middlemen traders subsequently sell to wholesalers and wholesalers then sell to exporters, channel II cocoa farmers sell to wholesalers and subsequent wholesalers sell to exporters and channel III farmers sell their cocoa beans to plant Mini Chokato. Total costs and marketing the largest margin of cocoa beans contained in the I channel Rp. 9.446,53/kgand Rp. 3.670,83/kg /kg, while the efficiency of marketing and farmer's share of marketing channels III more efficient when compared to marketing channels I and II in the amount of 29,06% and 100%. The problems faced by the fluctuations in the price, the quality of cocoa beans, the limitations of traders in calculating the water content of the cocoa beans and the limited capacity of the plant in the district of South Payakumbuh. Keywords: Cocoa beans, functions of marketing, channel marketing